Persistent Lower Limb Deformities Despite Amelioration of Rickets in X-Linked Hypophosphatemia (XLH) - A Prospective Observational Study - Mindler, Gabriel T.; Stauffer, Alexandra; Kranzl, Andreas; Penzkofer, Stefan; Ganger, Rudolf; Radler, Christof; Haeusler, Gabriele; Raimann, Adalbert (Frontiers in Endocrinology, 2022)
Background: Gait deviations, lower limb pain and joint stiffness represent key symptoms in patients with X-linked hypophosphatemia (XLH, OMIM 307800), a rare disorder of mineral homeostasis. While the pathomechanism for rickets is well understood, the direct role of PHEX (Phosphate-regulating neutral endopeptidase) deficiency in non-rachitic features including complex deformities, skull and dental affections remains unclear. FGF23-inhibiting antibody treatment can normalize serum phosphate levels and to improve rickets in XLH patients. However, linear growth remains impaired and effects on lower limb deformity and gait are insufficiently studied. Aims: To characterize and evaluate the course of lower limb deformity in a case series of pediatric XLH patients receiving Burosumab therapy. Methods: Comparative assessment of planar radiographs, gait analysis, biochemical and clinical features of pediatric patients before and ≥12 months after initiation of FGF23-inhibiting was performed prospectively. Lower limb maltorsion was quantified by torsional MRI and gait analysis. Standardized deformity analysis of lower limb anteroposterior radiographs was conducted. Results: Seven patients (age 9.0 +/-3.6 years) were eligible for this study. All patients received conventional treatment before onset of antibody treatment. Maltorsion of the femur was observed in 8/14 legs using torsional MRI (mean antetorsion 8.79°). Maltorsion of the tibia was observed in 9/14 legs (mean external torsion 2.8°). Gait analysis confirmed MRI findings with femoral external malrotation prior to and one year after onset of Burosumab therapy. Internal foot progression (intoeing gait) remained pathological in all cases (mean 2.2°). Knee rotation was pathologically internal 10/14 legs. Mean mechanical axis deviation (MAD) of 16.1mm prior to Burosumab changed in average by 3.9mm. Three children underwent guided growth procedures within the observation period. Mild postprocedural rebound of frontal axis deviation was observed under Burosumab treatment in one patient. Conclusions: This is the first study to investigate lower limb deformity parameters quantitatively in children with XLH receiving Burosumab. One year of Burosumab therapy was associated with persistent maltorsion and frontal axis deviation (varus/valgus) despite improved rickets in this small, prospective uncontrolled study.